Structural, vibrational and electronic properties in the glass-crystal transition of thin films Sb₇₀Te₃₀ doped with Sn - Bilovol, Vitaliy (2020)
Antimony-telluride based phase-change materials doped with Sn have been proposed to be ideal materials for improving the performance of phase-change memories. It is well known that Sb₇₀Te₃₀ thin films show a sharp fall in the electrical resistance in a narrow temperature range when heating. Therefore, it is interesting to study the effect of adding Sn into this composition. In this work, undoped and Sn-doped SbeTe thin films of composition Snₓ[Sb₀.₇₀Te₀.₃₀]₁₀₀₋ₓ, with x = 0.0, 2.5, 5.0 and 7.5 at. %, have been obtained by pulsed laser deposition. Their electrical resistance has been measured while heating from room temperature to 650 K. A sharp fall in the electrical resistance, associated to the glass-crystal transition, has been detected in all the samples within a narrow temperature range. The onset temperature of this transformation increases with the Sn content. Both as-obtained and thermally-treated films have been structurally characterized by X-ray and by Raman spectroscopy. We have compared the results among these compositions in terms of the identified crystallization products, transformation onset temperatures, transformation temperature ranges and amorphous/crystallized electrical resistance ratio. We have found that the frequency of the Raman modes decreases with Sndoping. Finally, in order to study the electronic structure and to determine the band gap, the frequencies of the allowed Raman modes and the vibration directions of the Sb₇₀Te₃₀ compound, Density Functional Theory based ab initio calculations have been performed as a function of the Sn concentration.